Penanaman Nilai-Nilai Nasionalisme Melalui Pembelajaran Pendidikan Kewarganegaraan Pada Mahasiswa (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The purpose of this research is to find out the importance of instilling Nationalism Values through learning civic education in students, building awareness of national identity and love for the country, and encouraging students as the nation's young generation to maintain nationalism values to overcome various problems faced by a nation. In addition, there are several challenges faced by Civic Education Lecturers in dealing with curriculum changes and learning strategies. The research approach or method used is a literature review of journals researched by the author.